Criticism of the fallacies of self-representation: Francisco Pacheco’s epigrams 3-6 on a portrait of Jerónimo Sánchez de Carranza (Minerva, 2021)
Ms. 9-2563 of the Library of the Royal Academy of History in Madrid contains a series of eight unpublished Latin epigrams written by Francisco Pacheco deriding the famous swordsman Jerónimo Sánchez de Carranza, author of Philosophia de las armas (Philosophy of Weapons, Sanlúcar de Barrameda, Cádiz, 1582). Amongst its aims, there is a criticism on the self-representation the swordsman sought to show publicly through the commissioning of a portrait by the painter Juan Bautista Vázquez el Viejo. This paper offers the critical edition, Spanish translation, and commentary of epigrams 3-6.
Keywords: Francisco Pacheco; Jerónimo Sánchez de Carranza; neo-Latin farcical epigrams; self-representation; Renaissance; Humanism; 16th century; Seville; Juan Bautista Vázquez El Viejo